Influence of Reservoir Diagenesis on Physical Properties - Shi , Chenhui (Scientific Journal of Technology, 2025)
Reservoir diagenesis is a core geological process that controls key physical properties such as porosity and permeability and determines the capacity of oil and gas storage and seepage. This paper systematically discusses the dual influence mechanism of diagenesis on the physical properties of reservoirs, reveals the causes of the strong heterogeneity of reservoirs, and explores its application value in geological exploration.Research indicates that diagenesis shapes the final reservoir space through both destructive and constructive processes. Destructive effects (such as mechanical and chemical compaction, siliceous and carbonate cementation) generally reduce primary porosity, among which the cementation of clay minerals such as illite causes particularly significant damage to permeability. Constructive effects (especially organic acid dissolution and structural fracture) are the key to forming secondary pores and improving the physical properties of deep and tight reservoirs. In the field of unconventional oil and gas, the study of diagenesis has significant guiding significance for evaluating the fracturing ability and fluid mobility of reservoirs.